Enhancing Managerial Decision-Making Quality through Activity-Based Costing: An Economic Perspective - Usman, Asri; Mediaty, Mediaty; Latjompo, Sri Mulyani; Rasak, Abdul; Azizah, Andi Nurul (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyse the contribution of Activity-Based Costing (ABC) to improving the quality of managerial decision-making, particularly within the manufacturing and service sectors. A systematic literature review (SLR) approach was employed, drawing data from databases such as Scopus, ScienceDirect, and Google Scholar, and focusing on publications from 2018 to 2025. Through a gradual selection process, 23 relevant articles were identified. The findings indicate that ABC effectively reduces cost distortions—such as under costing by up to 491%—enhances operational efficiency, and supports strategic decisions in areas such as pricing and cost control, leading to profitability improvements of up to 20–30% across various sectors. The study suggests that governments should support ABC adoption in small and medium-sized enterprises (SMEs) through subsidy policies and digitalisation initiatives. For businesses, the implementation of ABC can foster competitiveness and innovation, thereby strengthening the local economy through more accurate and data-driven decision-making. This research contributes new insights by integrating ABC into the context of Industry 4.0, highlighting the potential of technologies such as artificial intelligence (AI) to address traditional challenges, including resistance to change and reliance on manual data processing.